Rereading the territory of mother's guardianship in Islamic jurisprudence - seyednaghi mousavi; yaser naderali (فقه و حقوق خانواده)
In the current age, family research is doubly necessary in the civilization confrontation and secular civilization, and the formulation of legal, jurisprudential and educational theories in this field, especially regarding the role and duties of the mother, is emphasized in a methodical manner by relying on the Islamic and jurisprudential tradition. There are long-term discussions about the mother in Islamic jurisprudence, and the issue of guardianship and the circle of influence and control of the mother in the affairs of the child is one of the most important. In the popular view, the mother's guardianship over the child is limited. The present article tries to reread the territory of mother's guardian's ship (independent and non-independent) in Islamic jurisprudence and examine it based on deductive ( Ijtehadi) method. After the investigations, it was concluded that the independent guardianship of the mother is a sign of compliance with the proofs of custody as well as a sign of the commitment of educational applications. Also, the mother as one of the 'Adul al Mo'minin (followers of the believers) has independent guardianship and can have non-independent guardianship (Mazoon) only through guardianship. Also, it was concluded that the territory of the mother's guardianship is dependent on the reason that proved it and it will be decisive in the assumption of confluence with the father's guardianship, and various assumptions of the confluence of the mother's guardianship with the father's guardianship were examined